Assessment of the Use and Status of New Drug Information Centers in a Developing Country, Ethiopia: The Case of Public University Hospital Drug Information Centers - Melaku, Tadesse; Yilma, Zewdu; Reshid, Elham; Ashenef, Ayenew; Chane, Tesfahun (BioMed research international, 2018)
Introduction. Drug information center (DIC), in most cases, is part and parcel of pharmacy service established as a unit that deals with offering recent, balanced, truthful facts about drugs to the public, patients, and health care professionals. Objective. To assess the query receiving and response trends by the drug information centers (DICs) found in main university affiliated teaching health care institutes in Ethiopia. Settings. The drug information centers located in Mekelle, Gondar, Jimma, Tikur Anbessa Specialized University Hospitals, and St. Peter Public Hospital, Ethiopia. Methods. It employed analytical, descriptive (cross-sectional), and retrospective methods. The study was performed from June to August, 2015. All the available documented data were gathered with the help of checklist and questionnaire (self-administered). Results. A total of 439 queries submitted to the DICs during their active service period were included in this study of which 407 were found to be suitable for this assessment. The highest inquiries had come from public hospitals (60 %) from health care workers (95.1 %), out of which pharmacists were the highest (63.57 %) submitters, followed by health care students (12.7 %). The major purposes of query submission were to improve treatment outcome of patients (33.9 %) and then to update the knowledge (25.1 %) although 39.3 % of the queries did not document it. The most common requests concern drug interaction (19.7 %) followed by therapeutic use (17.8 %) and the major pharmacological group is about antimicrobials (23.3 %) followed by antihypertensives (11.4 %). Web sites (31.4 %) were the most highly used references followed by Micromedex (19.0 %). Conclusion. The assessment of the DICs had shown that it is feasible to establish and develop DIC services in a developing country setting, Ethiopia. The study found that most of the common queries deal with drug interaction, therapeutic use, and general product information (most commonly about antimicrobials).